STRATEGI SDM DAN IMPLIKASINYA TERHADAP KEGIATAN REKRUTMEN, SELEKSI DAN PENGEMBANGAN DI UNIKA SANTO THOMAS MEDAN - Tinambunan, Anitha Paulina; Munthe, Kornel; Tarigan, Miska Irani (UNIKA Santo Thomas, 2023)
HR strategy is an effort to provide HR that has high competence and commitment to the company. Changes in HR strategy are not taboo but need to be done with careful consideration. If recruitment, selection and training activities are not based on HR strategy, it will disrupt the teaching and learning process in the future. The formulation of the problem in this research is: 1. What HR strategies does Unika Santo Thomas Medan implement?; 2. What are the implications of these HR strategies for recruitment, selection and training activities at Unika Santo Thomas Medan? When viewed from Sommenfeld and Pelper's theory, Unika Santo Thomas Medan's HR strategy varies according to the stage of its life cycle. In the early stages of operation until 2000, the strategy used was the Club type; 2001 - 2014 used the Fortress strategy while 2015 until now uses the Academy strategy. The recruitment and selection system is necessary to prepare reliable human resources who are able to assist the business in achieving its goals. To fill vacant positions, Unika Santo Thomas Medan uses traditional recruitment methods through Employee Referral and Advertisement. Online recruitment methods include: Job Posting and Job Bidding. Since 2018 the selection of Lecturers and Tendik Unika Santo Thomas Medan has been carried out collectively. Previously, the acceptance of Lecturers and Tendik was carried out depending on the needs of the faculty/division. The selection method carried out by Unika Santo Thomas Medan is categorized as scientific because it consists of several stages, namely: Application Letter Check; Recommendation Check and Reference Check; Job Interview; Selection and Placement Decision. Training is a short-term learning to improve the knowledge and skills of an employee. The training methods conducted by Unika Santo Thomas Medan consist of: Instructor briefing; On-the-job-training (OJT) and Job Rotation.